Kinetic, mechanistic and thermodynamic investigations on Iridium (III) catalyzed oxidation of D-Mannitol by N-chloro-p-toluenesulfonamide in perchloric acid medium - J. Pandey; A. Verma; R. Patel; Sh. Srivastava (Iranian Journal of Chemical Engineering)
The present paper deals with the kinetics and mechanism of homogeneously Ir(III) chloride catalyzed oxidation of D-mannitol by chloramine-T [CAT] in perchloric acid medium in the temperature range of 30 to 45 0C. The reaction is carried out in the presence of mercuric acetate as a scavenger for chloride ion. The experimental results show first order kinetics with respect to the oxidant [CAT] and catalyst [Ir(III)] while zero order with respect to substrate, i.e., D-Mannitol was observed. The reaction shows negligible effect of [Hg(OAc)2], [H+] and ionic strength of the medium. Chloride ion positively influence the rate of reaction. The reaction between chloramine-T and D-Mannitol in acid medium shows 2:1 stoichiometry. To calculate activation parameters, the reactions have been studied at four different temperatures between 30 to 45ºC. A mechanism involving the complex formation between catalyst and oxidant has been proposed. Mannonic acid has been identified chromatographically and spectroscopically as the final product of oxidation of D-Mannitol. Based on the kinetic data, reaction stoichiometry and product analysis, a reaction mechanism has been proposed and rate law has been derived.